2019
DOI: 10.1016/j.schres.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Insight and risk of suicidal behaviour in two first-episode psychosis cohorts: Effects of previous suicide attempts and depression

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 94 publications
(110 reference statements)
3
33
3
Order By: Relevance
“…Inconsistently with what previously reported in comparable FEP studies, we found no associations of baseline suicidal ideation with positive symptoms and insight (as measured with PANSS “Lack of judgment and insight” item subscore). In contrast, Lopez‐Morinigo et al () supported the role of insight in attempted suicide during FEP. Moreover, Robinson et al () observed that greater insight was a relevant predictor of suicide attempts in FEP patients.…”
Section: Discussionmentioning
confidence: 93%
“…Inconsistently with what previously reported in comparable FEP studies, we found no associations of baseline suicidal ideation with positive symptoms and insight (as measured with PANSS “Lack of judgment and insight” item subscore). In contrast, Lopez‐Morinigo et al () supported the role of insight in attempted suicide during FEP. Moreover, Robinson et al () observed that greater insight was a relevant predictor of suicide attempts in FEP patients.…”
Section: Discussionmentioning
confidence: 93%
“…Although this links neatly with metacognition and confidence, it runs counter to received clinical folklore that the gaining of insight, particularly after a psychotic episode, induces depression and at worst, may even lead to suicide. Empirical justification for unidirectional causality is lacking, 16 perhaps because of the messy complicating factors that often precede suicide in people with psychosis in the real world: longstanding depression, rejection of treatment and disengagement with social and professional support. These factors attest more to the loss of insight than its gain, notwithstanding the pain attached to the latter.…”
Section: Insight and Metacognitionmentioning
confidence: 99%
“…Specifically, the WAIS-IV [30] is administered by a MSc-level clinical psychologist (VGRR) in order to rule out an IQ ≤ 70, which is an exclusion criterion. Those with an IQ > 70 are administered the Trail Making Test (TMT) [31], which assesses executive function and has been found to correlate with insight scores in psychosis patients [32], by VGRR shortly after the WAIS-IV in order to complete the baseline neurocognitive assessment at this point.…”
Section: Recruitment Processmentioning
confidence: 99%
“…Given that the mean SAI-E score for psychosis patients is 13/28 with a standard deviation of around 6 [32,35], a difference of 2 points (e.g., 13 vs. 15) between groups (e.g., MCT vs. controls), which is considered to be clinically meaningful [26], is equivalent to an effect size of 0.33 with a two-tailed alpha significant level set at 5%. Under these assumptions, for reaching a sufficient statistical power of β = 80% at the end of the study, we will need n = 63 subjects in each arm, that is, a total sample size of N = 126 patients, who will be analysed at the end of the study on an intention-to-treat (ITT) basis.…”
Section: Power Calculations and Estimation Of Sample Sizementioning
confidence: 99%
See 1 more Smart Citation